PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN BANK PERKREDITAN RAKYAT (BPR) ARTHA HUDA ABADI PATI (Studi Kasus pada Bagian Pemasaran BPR Artha Huda Abadi Pati) - Alfian Ari Widiyanto; Wahyu Hidayat (Universitas Diponegoro, 2017)
Organization culture in the company can be a guide for the employee to doing the job and norms behavior. So as motivation is an important element in the company to improve employee performance. Aim for this research is to describe and analyze influence organization culture and motivation to employee performance in PT. BPR Artha Huda Abadi Pati. This research used 74 PT BPR Artha Huda Abadi Pati marketing departemen employee as a population and respondents. Sampling technique used in this research is by using non-probability sampling technique that is Purposive Sampling. Analysis method to process the data is using correlation coefficient, determinant coefficient, simple linear regression, and double linear regression, T-Test, F-Test with SPSS V.16 program. The result of analyzing data organization culture and motivation id take effect to employee performance. Organization culture and motivation can describe variable of employee’s performance amount to 40,4%. Organization culture can explain employee performance amount to 28,6%, while motivation can explain amount to 20,2%. Organization culture and motivation together affect to the employee’s performance. Conclusion from this research is organization culture and motivation partially have effect to the PT. BPR Artha Huda Abadi Pati employee’s performance. Suggestion that can be give is how the company can create good corporate order so that employees can work well and discipline in work, give direction employees to the culture of all K3 (Satisfaction, Safety and Health) and good communication and provision of better facilities.